RANCANG BANGUN INDUSTRI TEPUNG LIDAH BUAYA (Aloe vera) TERPADU - Tri Yuni Hendrawati, Eriyatno, Machfud, Koesnandar, Illah Sailah dan Titi Candra Sunarti (Department of Agroindustrial Technology, Bogor Agricultural University, 2007)
ABSTRACTTechnology to produce Aloe vera powder has been implemented in Aloe vera centre (AVC), Pontianak, West Kalimantan in pilot-plant scale. Based on chemical analysis and biological activity test, Aloe vera powder can be used to formulate cosmetic, food and pharmaceutical products such as lotion, shampo, soap, food supplement, sun burn cream and healing. Based on AVC technology pilot plant, research on designing an integrated Aloe vera powder industry has been conducted with system approach which the aim was to establish its decision supporting system and design engineering of Aloe vera industry in optimum scale. The research finding indicated that the application of system was able to synthesize ideas of interdiciplines; therefore it would improve the effectiveness of decision-making integratively. The research produced decision-supporting system model of integrated Aloe vera powder industry that accommodate the needs of stakeholders and should be effectively used by the decision makers facing dynamic change and information development. The research also produced process engineering flow diagram and layout of Aloe vera industry plant at economic optimum capacity. These models includes the evaluation of the best Aloe vera product, the best location of industry, material and energy balance, choise of specification of apparatus. This model can analyze the feasiability of Aloe vera powder industry in various capacities and optimize the economic capacity scale. To prevent farmer from decreasing Aloe vera price, this model designed win-win solution cost between industry and farmer to keep sustainability of industry and increasing farmers income. This model can also calculate the farm to save industry in raw material sustainability. Financial analysis with case study in Aloe vera Centre, Pontianak, West Kalimantan, shows that optimum capacity 25 ton powder/year, raw material 1852 ton Aloe vera/year (minimum farm 26 ha) with yield 1,35%, production periode 8 hours/day, 240 days/year and feasible with Pay Back Period 4,04 years, Break Even Point 13,568 ton powder/year, Net B/C 2,00, IRR 36,96% and feasible.. Win-win solution price of Aloe vera Rp.1100,-/kg Aloe vera. Sensitivity analysis shows that limit of decreasing product price 26.43% from normal price and limit of increasing raw material price Rp.3400/kg Aloe vera (normal price Rp.1100,-). Keywords : design, model, decision supporting system, integrated aloevera powder industry.